Biomass (Amritsagar) derived efficient solid base catalyst for eco-friendly biodiesel synthesis: A study on synthesis, reaction kinetics, and thermodynamic properties - Bidangshri Basumatary; Biswajit Nath; Bipul Das; Anjana Dhar; Sanjay Basumatary (Next Sustainability)
This study examines the effectiveness of a heterogeneous catalyst derived from the Amritsagar (AAA) banana plant in the synthesis of biodiesel using Jatropha curcas oil. The fruit peel, rhizome, and stem of the post-harvest Amritsagar (AAA) plant were calcined at 550°C and utilized as catalysts for transesterification. The catalysts are characterized using advanced analytical instruments and techniques such as FESEM, HRTEM, EDX, FT-IR, XPS, XRD, and BET. The most effective catalyst identified in this work is the Amritsagar calcined peel catalyst at 550 °C (ACP-550). Its characterization confirms the existence of Ca, K, Si, Fe, Na, Sr, Mn, Mg, and Zn metal oxides and carbonates, and it reveals a BET surface area of 26.104 m²/g. The catalyst ACP-550 outperformed the other catalysts, delivering a biodiesel yield of 97.58 % at 65 °C under optimal conditions, which comprised a 9:1 methanol to oil molar ratio, 7 wt% catalyst, and a 20 min reaction time. The study also includes an investigation of basicity, turnover frequency, soluble alkalinity, pH measurement of catalysts, reaction kinetics, thermodynamic parameters, reusability tests, and a comparison of catalytic activity of the catalysts in the production of biodiesel. The synthesized biodiesel was characterized through GC-MS NMR, and FT-IR analysis. Moreover, the assessment of fuel characteristics of biodiesel obtained from Jatropha curcas oil (JCO) was documented and compared with international standards and the properties were found to be within the specified limits.